Differences in Attitudes About HIV Pre-Exposure Prophylaxis Use Among Stimulant Versus Alcohol Using Men Who Have Sex with Men. - Oldenburg, Catherine E; Mitty, Jennifer A; Biello, Katie B; Closson, Elizabeth F; Safren, Steven A; Mayer, Kenneth H; Mimiaga, Matthew J (AIDS and behavior, 2015)
Alcohol and stimulant use are independently associated with increased HIV acquisition among men who have sex with men (MSM). We assessed differences in acceptability and perceived barriers to uptake of pre-exposure prophylaxis (PrEP) among stimulant and alcohol-using MSM in Boston. From September 2012-2013, a quantitative assessment was conducted with 254 MSM respondents who reported recent condomless sex in the context of concurrent stimulant (crack/cocaine and crystal methamphetamine; n = 132) or alcohol use (n = 122). Thirteen (5.1  %) reported previous PrEP use. In multivariable models, stimulant users were more likely to be concerned that substance use would affect PrEP adherence (aRR = 2.79, 95  % CI 1.63-4.77), and were less concerned about HIV stigma as a barrier to PrEP uptake (aRR = 0.52, 95  % CI 0.30-0.90) compared to alcohol users. Barriers to PrEP uptake and adherence differ by type of substance used. Different strategies may be required for PrEP implementation among MSM who use stimulants and alcohol.